Tathwîr Al-Washîlah Al-Ta’Alîmiyah Al-Fukâhi Li Ta’allum Mahârah Al-Qirâ’ah - Yuyun Rahmatul Uyuni; Ubaidillah Ubaidillah (al-Ittijah : Jurnal Keilmuan dan Kependidikan Bahasa Arab, 2021)
This research aims to develop the comic educational method for teaching reading in the seventh grade at Al-Jawhara Al-Naqiya Intermediate Islamic School, Cibeber Cilegon. Moreover, knowing the effectiveness of the humorous educational method for teaching the skill of reading in the seventh grade of the Al-Jawhara Al-Naqiya Intermediate Islamic School, Cibeber Cilegon. To achieve the purpose above, the researcher uses the Borg and Gall development theory to achieve the purpose above and uses the research to a type of Research and Development (R&D) that refers to the Borg and Gall model using six steps in development. The community in this research is 105 students from the three semesters, and its sample is 26. The methods of data collection used in this research are observation, interview, and testing. As a result of developing the humorous educational method for learning the reading skill, the pretest result is seen at 61 and the post-test result 82. Therefore, the average score in reading skills was upgraded from the pretest to the post-test with 20.